Open Science News Informing System for Scientific Libraries - I. I. Ryabova (Библиосфера, 2024)
The purpose of the study is to theoretically and practically substantiate the need to introduce an online news information system into library practice as part of the information support of scientific activities (on the example of Open Science). The work theoretically substantiates that improving the news information system in libraries is necessary in connection with the development of technology, open science, library activities and the rapid growth of disparate sources of information. The experience analysis of 130 libraries in presenting various news information products has led to the conclusion that the implementation of news information requires appropriate technology that would allow us to model the sequence of processes and operations for generating news library and information products.As a result the model of a news information system on open science is developed, which allows searching, collecting, processing, and synthesizing news information on open science, as well as creating, posting and distributing information products, their qualitative and quantitative assessment of effectiveness to be made. It has been implemented on the web platform of the State Public Library for Science and Technology of the Siberian Branch of RAS “Library for Open Science” in January 2023 and demonstrates a gradual increase in the number of all web analytical indicators of news information products created on its basis.